2015
DOI: 10.1590/0004-282x20150109
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA for trigeminal neuralgia: a review of the available data

Abstract: Trigeminal neuralgia (TN) is a unilateral disorder characterized by brief electric-shock-like attacks of pain, abrupt in onset and termination and limited to the distribution of one or more divisions of the trigeminal nerve 1 . It is reported to have a prevalence of 0.1-0.2 per thousand and an incidence ranging from about 2 to 7.1/100 000/year and extending up to 20/100 000/year in individuals over 60 years of age. The condition is more common in women than in men (ratio 3:2) 2 . Treatment includes pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
15
0
3
Order By: Relevance
“…A few small randomized clinical trials have been conducted and also suggested that botulinum toxin may be helpful in the treatment of neuropathic pain, namely painful peripheral diabetic neuropathy (20), CRPS (21), and trigeminal neuralgia (22). For the same reasons botulinum toxin has been used elsewhere in the body to help manage uncontrolled neuropathic pain, extraoral use in the orofacial region has been explored (23). While the exact mechanism for analgesic effect in such patients is not known, the adverse effects of botulinum toxin are generally minor and local to the injected tissues, such as dryness and muscle asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…A few small randomized clinical trials have been conducted and also suggested that botulinum toxin may be helpful in the treatment of neuropathic pain, namely painful peripheral diabetic neuropathy (20), CRPS (21), and trigeminal neuralgia (22). For the same reasons botulinum toxin has been used elsewhere in the body to help manage uncontrolled neuropathic pain, extraoral use in the orofacial region has been explored (23). While the exact mechanism for analgesic effect in such patients is not known, the adverse effects of botulinum toxin are generally minor and local to the injected tissues, such as dryness and muscle asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2002, there have been many reports concerning BTX-A treatment for TN [ 9 19 ]. Several randomized clinical studies have focused on efficacy and safety issues [ 25 ]. These findings have triggered much interest in clarifying questions such as the optimal dose, duration of therapeutic efficacy, and common adverse reactions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of BTX-A to relieve TN was first reported in 2002, and its safety and effectiveness was later confirmed by series studies [3][4][5][6][7][8][9][10][11][12][13]. In 2012, our team conducted the first RCT study in this field, and obtained the prima facie evidence of BTX-A for TN.…”
Section: Commentarymentioning
confidence: 93%